2010
DOI: 10.1016/j.tcb.2010.03.002
|View full text |Cite
|
Sign up to set email alerts
|

The Beclin 1–VPS34 complex – at the crossroads of autophagy and beyond

Abstract: An increasing body of research on autophagy provides overwhelming evidence for its connection to various biological functions and human diseases. Beclin 1 is the first described mammalian autophagy protein and appears to act as a nexus point between autophagy, endosomal, and perhaps also cell death pathways. Beclin 1 performs these roles as part of a core complex that contains vacuolar sorting protein 34 (VPS34), a class III phosphatidylinositol-3 kinase. The precise mechanism of Beclin 1-mediated regulation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
612
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 683 publications
(626 citation statements)
references
References 55 publications
(108 reference statements)
12
612
1
1
Order By: Relevance
“…1 BCL2, an inhibitory factor in autophagy, binds to the BCL2-binding domain of BECN1 to suppress this complex. 26 In our study, SLC9A3R1 was found to reduce the integration between BECN1 and BCL2 via its interaction with BECN1 (Fig. 4).…”
Section: Discussionsupporting
confidence: 56%
“…1 BCL2, an inhibitory factor in autophagy, binds to the BCL2-binding domain of BECN1 to suppress this complex. 26 In our study, SLC9A3R1 was found to reduce the integration between BECN1 and BCL2 via its interaction with BECN1 (Fig. 4).…”
Section: Discussionsupporting
confidence: 56%
“…The stratification can be viewed based on their interaction and stability: PIK3C3-PIK3R4-BECN1, the most stable and prevalent complex, constitutes the core; while ATG14 and UVRAG (UV radiation resistance associated) are combined with the core in PtdIns3K complex I (PtdIns3K-C1; ATG14-containing PtdIns3K complex) and PtdIns3K complex II (PtdIns3K-C2; UVRAG-containing PtdIns3K complex), respectively; 75-78 KIAA0226/Rubicon is a regulatory subunit that is thought to stably bind to UVRAGcontaining complexes; 77,78 AMBRA1, NRBF2 (nuclear receptor binding factor 2) and other accessory factors transiently or unstably interact with either BECN1 (e.g., AMBRA1) 79,80 or ATG14 (e.g., NRBF2), [81][82][83] thus comprising the peripheral components. 84,85 UVRAG also exists in a separate complex excluding ATG14, which holds an important role in the regulation of autophagy at the maturation step. 84,86 Atg14/ATG14 and Vps38/UVRAG are present exclusively in 2 Vps34/PIK3C3 complexes (PtdIns3K complex I and II in yeast, and class III PtdIns3K-C1 and PtdIns3K-C2 in mammalian cells, respectively), which are organized in similar V-shape conformations with Vps15/PIK3R4 at the base.…”
Section: Regulation Of Autophagy By Class III Ptdins3kmentioning
confidence: 99%
“…84,85 UVRAG also exists in a separate complex excluding ATG14, which holds an important role in the regulation of autophagy at the maturation step. 84,86 Atg14/ATG14 and Vps38/UVRAG are present exclusively in 2 Vps34/PIK3C3 complexes (PtdIns3K complex I and II in yeast, and class III PtdIns3K-C1 and PtdIns3K-C2 in mammalian cells, respectively), which are organized in similar V-shape conformations with Vps15/PIK3R4 at the base. 87 In yeast, PtdIns3K complex I and II play a role in autophagy and the vacuolar protein sorting pathway, respectively.…”
Section: Regulation Of Autophagy By Class III Ptdins3kmentioning
confidence: 99%
“…6 This conserved complex consists of vacuolar protein sorting 34 (Vps34; also known as Pik3c3), Atg6/Becn1 (also known as Vps30 in yeast), and the serine-threonine kinase Vps15/ird1 (p150 in mammals; also known as Pik3r4). 7,8 Localized production of PI3P by Vps34 can act to recruit proteins containing PX or FYVE domains to membrane compartments, such as the autophagosome isolation membrane. 9 Vps34 is also required more broadly for several vesicular trafficking processes such as the sorting of hydrolytic enzymes to the yeast vacuole and mammalian lysosome, and endocytic trafficking.…”
mentioning
confidence: 99%